Effect of nanometer silicon dioxide on the frictional behavior of lubricating grease. (14th August 2017) - He, Qiang; Li, Anling; Guo, Yachen; Liu, Songfeng; Kong, L-H
Nanometer-silicon dioxide encapsulated in lithium grease is prepared, and the frictional behavior of the lithium grease and nanometer-silicon dioxide–contained lithium grease is compared with respect to the additive content, load, and frictional temperature in this article. The structure and morphology of nanometer-silicon dioxide is characterized by X-ray diffraction and scanning electron microscopy, respectively. Friction and wear tests were conducted on a four-ball friction and wear tester. The morphology of worn steel surface is analyzed by scanning electron microscopy and three-dimensional surface profiler. Results show that the addition of nanometer-silicon dioxide in grease can markedly improve the friction-reducing performance and anti-wear ability of base grease. When the nanometer-silicon dioxide in grease is 0.3 wt%, the friction coefficient and wear scar diameter decrease by 26% and 7% compared with base grease, respectively. The nanometer-silicon dioxide (0.3 wt%)–contained grease exhibits the lowest average friction coefficient at the load of 342 N, which decreases by 39% as compared with that of base grease. The worn surface is quite smooth with few shallow furrows and the wear scar diameter decreases under the lubrication of the grease containing 0.3 wt% nanometer-silicon dioxide. Moreover, it was found that the nanometer-silicon dioxide have been incorporated into the surface protective and lubricious layer by energy dispersive spectrometer analysis.